PENGARUH PENDAPATAN, DANA TALANGAN HAJI DAN RELIGIUSITAS TERHADAP KEPUTUSAN NASABAH MENDAFTAR HAJI - Fitriyah, Faridatul (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2016)
The article was written to understanding of the factor that influence muslims in Tulungagung registering worship hajj. Research in this article begins fidgetiness some muslim will be the waiting list worship hajj. Income the people in Tulungagung relatively increased every year, and activity religion relatively high greatly effect some muslims to registering wohship hajj. Coupled with the ease of facility credit for worship hajj for the poor. This all lead to decision making, especially nasabah credit to register worship hajj. The result reveals that the factor influenced nasabah decided to departure are credit worship hajj is and religiousity.